Pengaruh Penjarangan Beri terhadap Kualitas dan Kuantitas Hasil Buah Anggur (Vitis vinifera L.) Varietas Kediri Kuning - YUDHA, MADE KAMASAN DHARMA; SUKEWIJAYA, I MADE; DHARMA, I PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
The Effect of Berry Thinning on the Quality and Quantity of Grapes Yield ( Vitis vinifera L.) Kediri Kuning Variety Grapes are a horticultural commodity that have the potential to increase farmers' income. Efforts can be made to improve the quality and quantity of the Kediri Kuning grapes by thinning the berries by 10% – 60%. This study aims to determine the effect of thinning berries on the quality and quantity of a grapes and determine the best thinning treatment that can increase the quality and quantity of Kediri Kuning grapes. This study used Randomized Block Design with berry thinning treatment consisting of 4 levels, namely control (P0), thinning of 10 -25% (P1), thinning of >25-40% (P2), thinning of >40-60% (P3) at the age of berries 14 days after anthesis. The thinning method is cutting the berries in bunches using small scissors. The results showed that the treatment of thinning gave a very significant effect on variable weight of the fruit per bunch, berries weight, diameter berries, bunches length, vitamin C, sugar content of fruit ( o Brix), the content of total acid, and organoleptic. The best thinning of berries on the Kediri Kuning grapes was thinning treatment >40% - 60% (P3) which gave the highest quality and quantity, each fruit weight per bunch 290.65 g, berry weight 7.93 g, berry diameter 14.82 mm, the length of the bunch was 25.92 cm and the chemical content.